Pengenalan Coding Membuat Game pada Siswa Sekolah Dasar menggunakan Scratch - Istiqomah, Nalar; Fanny Novika (Politeknik Piksi Ganesha Indonesia, 2024)
In the digital age, both adults and children are accustomed to using gadgets with Internet capabilities. The things that children access the most are games. In fact, using gadgets too often will have a negative impact on both physical and mental health. Instead of just playing games, children should be encouraged to learn how to make games. This has many benefits, including practicing computational thinking, problem solving, and perseverance. Therefore, this PkM activity was conducted with the aim of introducing coding skills to children. This activity was conducted online using Zoom. Participants learned together to create games using Scratch, such as those available at bit.ly/GameKasir. Of the 19 participants who attended, 100% were satisfied with the activities provided and were even interested in learning more about coding. This shows that PkM activities can introduce coding to children in a fun way, and can even motivate participants to continue learning coding.